Republic of Estonia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This paper assesses Estonia's flexibility from two angles. The paper focuses on one aspect of that performance-the ability to sustain competitiveness. Then, a more forward-looking angle is the flexibility of Estonia's labor and product markets. Estonia has made great progress in achieving real convergence in the last decade. Current account deficits are integral to convergence. A key question raised by this analysis is whether the large external imbalances and the counterpart buildup in external obligations will be smoothly reversed.